A Case of Laparoscopic Mesenteric Cyst Excision. (4th September 2012) - Jain, Vikalp; DeMuro, Jonas P.; Geller, Matthew; Selbs, Elena; Romero, Carlos
Abstract : The objective of this study is to discuss the presentation, diagnosis, and surgical management of a young, healthy patient with a symptomatic mesenteric cyst. He had a 5-month history of abdominal pain from this disorder, and the case is presented to illustrate the clinical picture and operative management of this rare disorder.